USING TECHNOLOGY ACCEPTANCE MODEL TO ANALYSE THE SUCCESSFUL CROWDFUNDING LEARNING GAME CAMPAIGNS - Hong Huang; Han Yu; Wanwan Li; Jinxuan Ma (Інформаційні технології і засоби навчання)
Due to the limited opportunities for financial supports to educators, Crowdfunding can be an effective channel to solicit funding sources for educators to develop new learning games. Understanding user perceptions of a successful learning game guided by Technology Acceptance Model (TAM) could help educators to effectively adapt Information Communication Technologies (ICT) in developing more competitive learning games and secure more funding.  This study used a user survey to assess the success of Kickstarter-funded learning game projects. Guided by TAM, the study derives eight perceived assessment dimensions, including three Usefulness dimensions: Representation mode, Narrative, Interaction; four Usability dimensions: Learning provision, Skill building, Rules, Assessment; and one Acceptance dimension: Motivation. The analysis of the online assessment survey (n=115) revealed that successful funded learning game projects are focused on usefulness and usability. Users perceived a wider gap between successful and unsuccessful crowdfunding learning games in Learning Provision, Representation Mode, and Skill building. These enable game-based learning strategies by spelling out game rules that support learning provision in skill building, which is reflected in a detailed and in-depth narrative in a coherent representation layout. According to bivariate and multivariate analysis, among all eight dimensions, Representation mode, Interactivity, Skill building, Rules, Narrative and Learning provision are key factors that significantly associate with entrepreneurial success for the learning game development. A crowdfunding learning game TAM based perception evaluation model was developed based on perceived acceptance, usefulness and usability. This study examines the pedagogical aspects of using TAM to analyze crowdfunding learning games to help educators better use ICT to create new learning games that provide more customized, active, and flexible learning experiences, improve feedback and assessment, and increase involvement and access to game development.